KONSEP FITRAH DALAM PERSPEKTIF PENDIDIKAN ISLAM (ANALISIS KONSEP PENDIDIKAN ANAK MENURUT ABDULLAH NASHIH ULWAN) - Urip Bayanilah Imam (Oasis : Jurnal Ilmiah Kajian Islam, 2016)
The holy concept that is developed by much education expert and psychology recently more forward to side of cleaning soul someone. When he was born by mean. Not yet touch by alculturation and cause of ideologies that develop in this life. Therefore that concept fast is not walked how which meaning by Abdullah Nashih Ulwan that holy actually the concept of goodness by universal in by self it is believed of the only one Allah SWT. When baby ini fragrant, everyone was promes of tha onlu one it. It is not known by moslem or not moslem. The holy concept based on the holy Qur’an. It is developed by Abdullah Nashih Ulwan is that creation about the children education in moslem.The research method that is used is library research that has descriptif analysis forward meaning idol that has influence forward human life concept. The research result is : The holy concept according Abdullah Nashih Ulwan is goodness concept that is get in every children that is born in this earth by their mother. Where this concept influence to Tauhid of Allah SWT. The factors that cause happened the wrong holy is family environment (parents), school, social environtment, technology improved, and politic education and then the economical of country. As for the nature of a person developing a step taken is to optimize the potential of nature like education faith, moral, physical, ratio, psychological, social, and sexs.Keyword: The holy, The Holy in Islamic Education